Debating Political Rights: The Revocation of Former Convict's Rights to Be Elected in Indonesian Elections - Suarda, I Gede Widhiana; Anggono, Bayu Dwi; Setyawan, Fendi; Taniady, Vicko (Lentera Hukum, 2025)
The purpose of this article is to analyse the revocation of the political right of former convicts to candidacy as public officials in the Indonesian context based on positive law and decisions of the Indonesian Constitutional Court. In addition, this article aims to conduct a comparative study analysis of the issue, namely, between the arrangements in Indonesia and those in the United States and Australia. In Indonesia, everyone has the right to stand as a candidate for public office, including former prisoners, with certain conditions in accordance with positive law. However, the matter of revoking the political rights of former convicts remains a matter of debate, especially before the General Election. The Constitutional Court affirmed that the political right of former convicts to hold elected public office must fulfil several requirements. The political rights of former convicts are still guaranteed, but there are certain limitations. In Australia and the United States, the political rights of former convicts are also maintained, but with exceptions for some instances, such as corruption or treason against the state. Looking at the existing debate, it is necessary to safeguard civil and political rights universally, while paying attention to the specific cases that underlie the prohibition on former convicts from running for public office.KEYWORDS: Elections, Political Rights, Former Convicts.